Clinical Approach to Linear Hyperpigmentation: A Review Article - Alkhowailed MS; Otayf M; Albasseet A; Almousa A; Alajlan Z; Altalhab S (Dove Medical Press, 2021)
Mohammad S Alkhowailed,1 Mojahed Otayf,2 Abdulrahman Albasseet,2 Abdullah Almousa,2 Ziyad Alajlan,2 Saad Altalhab3 1Department of Dermatology, College of Medicine, Qassim University, Buraydah, Qassim, Saudi Arabia; 2College of Medicine, King Saud University, Riyadh, Saudi Arabia; 3Department of Dermatology, College of Medicine, Al-Imam Mohammad Ibn Saud Islamic University, Riyadh, Saudi ArabiaCorrespondence: Mohammad S AlkhowailedDepartment of Dermatology College of Medicine, Qassim University, Buraidah 52571, Qassim, Saudi ArabiaEmail m.alkhowailed@gmail.comAbstract: Linear hyperpigmentation is an unusual anatomical configuration in clinical dermatology. Owing to its rarity, consensus on the most effective method of classification is lacking. While linear hyperpigmentation generally follows Blaschko’s lines, this is not universal. Clinical findings such as adherence to Blaschko’s lines, associated morphological findings (including other cutaneous lesions), and systemic manifestations can be used to further characterize and diagnose variants of the disorder. Early detection of any underlying disease is vital, especially in cases with effective management, because the disorder may make it difficult to manage hyperpigmentation. Herein, we introduce a logical clinical diagnostic approach that represents a useful tool for dermatologists to efficiently evaluate patients presenting with linear hyperpigmentation. A simplified systematic and evidence-based approach is useful for this clinical condition owing to the heterogeneous causes and lack of specific diagnostic tools.Keywords: approach, blaschkitis, Blaschko’s lines, hyperpigmentation, linear, pigmentary mosaicism